Diversification, Systematic Risk, and Shareholder Return: A Capital Market Extension of Rumelt's 1974 Study - Lubatkin, Michael; Rogers, Ronald C. (Academy of Management Journal, 1989)
This study reexamined the performance outcome of diversification strategies by combining the advantages of security-market-based measures and Rumelt's classification scheme. The findings underscore...